KINERJA DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU DALAM PEMBINAAN ANAK JALANAN DI PEKANBARU - Kurnia Putra Jasty; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study was to determine the performance of the Department of Social and Pekanbaru City Cemetery under Development of Street Children in the city of Pekanbaru and to know what are the factors that hinder the performance of Department of Social Welfare and Development In Pekanbaru City Cemetery Street Children in the city of Pekanbaru in Pekanbaru . Theory (approach) is used as an analytical tool in this study is the theory of performance indicators efficiency , effectiveness , fairness , and responsiveness . While the methods used in this research is descriptive qualitative research that is intended to provide a systematic overview of the observed phenomena .Based on these results , Performance and Social Service Funeral Pekanbaru City , particularly the field of POM in dealing with street children is still not good . Efforts undertaken in the field of POM handle street children include coaching , mental guidance , and the provision of venture capital . However , the recruitment of street children conducted by the Department of Social Welfare and Funeral Pekanbaru City has not reached the desired target . Obstacles encountered in handling the business of street children is the attitude or mindset of street children who do not want to set a target , causing stunted POM field program . Another problem is the limited human resources in both the Department of Social and Pekanbaru City Cemetery is the source of the lack of budget funds . The process of mentoring street children street children should be done to the self . Supervision of the assistance also needs to be done. Keywords : efficiency , effectiveness , fairness , responsiveness